Female Agency in Selected Song Lyrics of Raye ‘My 21st Century Blues’ Album: A Critical Discourse Analysis - Fathimatuzzahra; Aisah; Hasra, Hasnini (Journal of English Teaching, Literature, and Applied Linguistics, 2025)
Music, as a form of cultural production, reflects and responds to societal values, making song lyrics a meaningful site for analysing social issues such as gender and power. This study investigates the representation of female agency in selected lyrics from Raye’s “My 21st Century Blues” album, with the aim of identifying how agency is constructed through the dominant transitivity processes. Using Fairclough’s three-dimensional framework of Critical Discourse Analysis and Abrams’ (1999) conceptualisation of female agency, this study analyses the clauses as the data of this study through Halliday’s transitivity system. The findings show that all types of processes were present in 310 clauses, with the material process as the most frequent (132 clauses or 42.58%), followed by relational and mental processes. Material processes frequently express self-direction, where the singer asserts autonomy through action, while relational and mental processes largely construct self-definition, revealing identity, reflection, and internal struggle. A discursive shift emerges from textual analysis, signalling how Raye positions herself within a particular discourse. These findings are further contextualised within the sociocultural practice of the music industry, where female artists often face marginalisation. Raye’s lyrics thus function as a powerful site for expressing female resistance, identity, and autonomy.